PEMBERDAYAAN ORANG TUA TERHADAP KEIKUTSERTAAN DETEKSI DINI TUMBUH KEMBANG BALITA DI PONDOK PESANTREN JAMILURRAHMAN AS-SALAFY - Ratna Wulan Purnami; Sri Astuti (ABDIMAS Madani, 2019)
Every parent wants children who are healthy, smart, quality and successful in the future, as well as every nation wants to have a next generation that is able to compete and excel amid the highly competitive global competition. The first five years of a child's life (infancy) is the most rapid growth and development of the human brain and a very sensitive period for the child's brain to receive various inputs from the surrounding environment. Early detection of growth and developmental deviations is an effort to prevent, stimulate and heal and recover. The purpose of this activity is to increase the participation of parents in the detection of growth and development of infants. The method used by conducting counseling, discussion and examination of child development. Counseling is done using the LCD and growth and development checks using a card to the health card (KMS) according to the sex of toddlers. The results of community service activities are there is an increase in understanding and awareness of parents in the early detection of growth and development in children and the results of 100% growth and development of toddlers in the normal category.